Revision of the Northern Shrimp (Pandalus borealis) on Flemish Cap in June 2003 - Río-Iglesias, José Luis del; Casas-Sánchez, José Miguel; González-Troncoso, Diana (2004)
Since 1988, a stratified random summer bottom trawl survey in Flemish Cap (NAFO Regulatory Area of Division 3M) was conducted by UE. In June 2003, the survey was carried out by the new research vessel R/V Vizconde de Eza, which will continue for this survey in the future. In order to calibrate the new ship, the comparative fishing trial (calibration) initiated in 2003 between the old research vessel R/V Cornide de Saavedra and the new R/V Vizconde de Eza, will continue during the survey in 2004. Because of this, the indexes in the series from 1988 to 2002 were not changed to the new scale by now. Still, the 2003 current indices from R/V Vizconde de Eza were transformed to the R/V Cornide de Saavedra scale, to make them comparable to the results obtained in previous years. The 2003 indexes were transformed by a length conversion method. The entire series of abundance, biomass, mean catch per tow and length distribution for northern shrimp (Pandalus borealis) are presented for the period 1988-2002, and the transformed data for the year 2003. In this year, a decreasing of shrimp biomass was observed. It was mainly due to declining of 3 and 5 age-classes. Also the youngest model groups (age 1 and 2) appeared well represented, predicting a good recruitment in next years. However, all these results must be taken carefully because the scarce number of hauls carried out during the calibration in 2003.